Applying the principle of 'la tazlimuna wa la tuzlamun' to al-qardh loan repayment after currency inflation‎ - Baihaqi , Muhammad; Bonang, Dahlia (Journal of Islamic Economics Lariba, 2025)
IntroductionIn the current fiat monetary system, inflation can severely diminish the value of money, causing injustice in long-term loan repayments. Within the Islamic economic framework, this raises significant concerns for al-qardh contracts—benevolent, interest-free loans—where delayed repayment may lead to harm for either the lender or borrower. The concept of la tazlimuna wa la tuzlamun (do not wrong others, nor be wronged) offers a moral foundation to seek fair and balanced repayment solutions in such contexts.ObjectivesThis study investigates how Islamic principles, particularly the notion of la tazlimuna wa la tuzlamun, can be applied to ensure justice in repaying al-qardh loans after currency inflation. The research aims to identify repayment models that uphold the lender’s rights without imposing undue burden on the borrower.MethodEmploying a normative and descriptive library research method, this study examines primary sources such as the Qur’an, Hadith, and classical Islamic jurisprudence, alongside contemporary scholarly works on Islamic economics and monetary systems. A thematic analysis was used to identify fair repayment mechanisms rooted in Islamic legal reasoning and public interest principles.ResultsThe study proposes several alternatives to address the injustice caused by currency devaluation, including adjusting loan values to the price of gold and silver, pegging debts to stable foreign currencies, applying inflation-based indexation, and discouraging hoarding behavior that exacerbates price instability. While the use of interest rates was explored, it was ultimately rejected by most Islamic scholars. The return to a gold-silver standard is presented as a long-term ideal to restore monetary fairness.ImplicationsThe findings offer practical guidance for Islamic financial ethics, suggesting the need for a formal fatwa to regulate fair debt repayment post-inflation. This guidance could extend beyond financial institutions to protect individuals and communities in inflationary environments, reinforcing justice and stability in Islamic economic transactions.Originality/NoveltyThis study provides a fresh perspective by integrating Islamic legal, economic, and ethical principles to address inflation-induced injustices in al-qardh repayment. It presents a balanced framework that respects the spirit of Islamic contracts while adapting to modern financial realities.